Predicting Job Crafting From the Socially Embedded Perspective: The Interactive Effect of Job Autonomy, Social Skill, and Employee Status. (December 2017) - Sekiguchi, Tomoki; Li, Jie; Hosomi, Masaki
Job crafting represents the bottom-up process of change employees make in their work boundaries and plays an important role in the management of organizational change. Following the socially embedded perspective, we examine the roles of job autonomy, social skill, and employee status in predicting job crafting. Study 1 with a sample of 509 part-time employees found that job autonomy and social skill not only directly but also interactively influenced job crafting. Study 2 with a sample of 564 full-time employees further revealed that job autonomy had a stronger impact on job crafting when employee status was high, but for those with a high level of social skill, job autonomy influenced job crafting regardless of the level of employee status. Our results suggest that managers and change agents can promote job crafting for organizational change by enhancing employees' ability to interact with others effectively, along with the increase of job autonomy.